2022
DOI: 10.4414/smw.2022.w30199
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an advanced practice nurse into a primary care practice: a qualitative analysis of experiences with changes in general practitioner professional roles in a Swiss multiprofessional primary care practice

Abstract: BACKGROUND: The complex care needs of people with chronic illnesses and multimorbidity pose a significant challenge to the Swiss primary care system. Ensuring efficient, high-quality care will require new care models. Internationally, the integration of advanced practice nurses (APNs) into primary care models has shown promising results. The current study investigates how general practitioners (GPs) in Switzerland experience the integration of APNs into their primary care teams with respect to their own profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In another Swiss cantons, projects similar to this project was developed a few years ago, but despite its positive evaluation, one of them was stopped because the relevant public health authorities decided not to continue supporting it [ 18 ]. The three other projects integrating advanced practice nurses also encounter difficulties in their sustainability due to an unsuitable legal framework and financing mechanisms [ 16 , 17 , 19 ]. Examples from other countries, such as Canada or the United States, have shown that the organizational transformation of PC models, particularly building new PC teams, must go hand in hand with a transformation in the financing model [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another Swiss cantons, projects similar to this project was developed a few years ago, but despite its positive evaluation, one of them was stopped because the relevant public health authorities decided not to continue supporting it [ 18 ]. The three other projects integrating advanced practice nurses also encounter difficulties in their sustainability due to an unsuitable legal framework and financing mechanisms [ 16 , 17 , 19 ]. Examples from other countries, such as Canada or the United States, have shown that the organizational transformation of PC models, particularly building new PC teams, must go hand in hand with a transformation in the financing model [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, transforming the country's PC model does not seem to be a necessity for many healthcare professionals, but for others, this transformation must occur by increasing the number of GPs trained in Switzerland [14,15]. Some isolated initiatives have transformed GP-centered PC models into interprofessional teams [16][17][18][19]. Some of them show promising results by integrating, for example, advanced practice nurses [16,17,20] or specialized nurses [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations